Optimisation of the Schizosaccharomyces pombe urg1 Expression System - Watson, Adam T.; Daigaku, Yasukazu; Mohebi, Saed; Etheridge, Thomas J.; Chahwan, Charly; Murray, Johanne M.; Carr, Antony M. (PloS one, 2013)
The ability to study protein function in vivo often relies on systems that regulate the presence and absence of the protein of interest. Two limitations for previously described transcriptional control systems that are used to regulate protein expression in fission yeast are: the time taken for inducing conditions to initiate transcription and the ability to achieve very low basal transcription in the "OFF-state". In previous work, we described a Cre recombination-mediated system that allows the rapid and efficient regulation of any gene of interest by the urg1 promoter, which has a dynamic range of approximately 75-fold and which is induced within 30-60 minutes of uracil addition. In this report we describe easy-to-use and versatile modules that can be exploited to significantly tune down Purg1 "OFF-levels" while maintaining an equivalent dynamic range. We also provide plasmids and tools for combining Purg1 transcriptional control with the auxin degron tag to help maintain a null-like phenotype. We demonstrate the utility of this system by improved regulation of HO-dependent site-specific DSB formation, by the regulation Rtf1-dependent replication fork arrest and by controlling Rhp18(Rad18)-dependent post replication repair.